Albumin fusion of thioredoxin - The production and evaluation of its biological activity for potential therapeutic applications - Ikuta, S.; Chuang, Victor; Ishima, Y.; Nakajou, K.; Furukawa, M.; Watanabe, H.; Maruyama, T.; Otagiri, M. (Elsevier, 2010)
Thioredoxin-1 (Trx) is a redox-active protein with anti-inflammatory effects. The effect of albumin fusion on the pharmacokinetic and pharmacodynamic properties of Trx was evaluated in this study. The findings indicate that the properties of human serum albumin and the fusion protein are comparable. The fusion protein showed similar plasma concentration and organ distribution profiles as human serum albumin. The fusion protein accumulated in lungs, reaching levels higher than Trx. In an insulin reducing assay, the activity of the fusion protein was 60% of the activity of Trx. However, survival rate of endotoxic shock mice induced by the administration of a lipopolysaccharide and D-galactosamine for fusion protein was double that of Trx. The findings reported herein indicate that the fusion protein is likely to have great clinical applications in areas such as the treatment of reperfusion injuries.